RESTORASI ARSIP KONVENSIONAL DI SUB DIREKTORAT RESTORASI ARSIP KONVENSIONAL ARSIP NASIONAL REPUBLIK INDONESIA - , CICILIA INDIRA A; , Dra. Eny Kusumindarti W ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The final report describes the conventional archives restoration at Sub Direktorat Conventional Archives Restoration National Archive of the Republic of Indonesia. The main goal of this restoration project is to save the archive conventional physical information and records that are attached to conventional media. This final report uses three methods. These methods comple ment each other so as to produce the data and information that is precise and accurate. Those three methods are literature review, interview, and observations. Literature review is to use reference books, records to collect data. While interview is direct interview with the authorities to complement data. Next is observation that use to make direct observation in the field during a restoration archive. The main conclusion of this report is the conventional archive restoration project is needed to protect the records from damage and repairing damaged archives so the content of the information could still be preserved and used. There are various methods used to repair the archives. Implementation of the restoration process which is done by ANRI are laminate, conqueror, lamatech cloth, leafcasting and encapsulation.